Pleural Mesothelioma Surveillance: Validity of Cases from a Tumour Registry. Issue 2 (2012) - Labrèche, France; Case, Bruce W; Ostiguy, Gaston; Chalaoui, Jean; Camus, Michel; Siemiatycki, Jack
Abstract : BACKGROUND: Pleural mesothelioma is a rare tumour associated with exposure to asbestos fibres. Fewer than than one-quarter of cases registered in the Quebec Tumour Registry (QTR) have been compensated as work-related. While establishing a surveillance system, this led to questioning as to whether there has been over-registration of cases that are not authentic pleural mesotheliomas in the QTR. OBJECTIVE: To assess whether registered cases of pleural mesothelioma could be confirmed. METHODS: A medical chart review was designed to assess the proportion of mesothelioma cases newly registered in the QTR in 2001/2002 that could be confirmed. For each registered case, clinical, medical imaging and pathology information were sought and, occasionally, additional immunohistochemistry staining was obtained. Three specialists – a chest physician, a radiologist and a pathologist – reviewed the available information and material, coding each mesothelioma case as to degree of certainty of the mesothelioma diagnosis. RESULTS: The QTR reported 190 incident cases of mesothelioma (81% males) for the period. The specialists classified 81% of charts as 'certain/probable'or 'possible' mesotheliomas, 8% as 'unlikely to be a mesothelioma' and 11% as 'not a mesothelioma'. After excluding chart summaries of unsatisfactory quality, 87% to 88% of the charts were classified as 'certain/probable' or 'possible' mesotheliomas, and 9% to 11% were still considered 'not a mesothelioma'. CONCLUSION: Tumour registry data are a valid source of information for mesothelioma surveillance. While there is some over-registration of mesothelioma cases in the QTR, a significant majority of registered cases appeared to be authentic. Over-registration cannot explain the greater proportion of cases that were not compensated.